Develop the Region's Economy Through Non-Traditional Types of Tourism - Jalolov Farhod Vohidovich (Researchparks Publishing, 2023)
This paper outlines the possibilities for developing non-traditional tourism in Uzbekistan using the world experience in tourism. And also analyzes the economic state of tourism in Uzbekistan and its opportunities.